2014
DOI: 10.4314/tjpr.v13i5.24
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effectiveness of Selected Vranac Wines Against Six Gram-Positive and Six Gram-Negative Bacterial Strains

Abstract: P. aeruginosa, S. enteritidis, S. sonnei and P. vulgaris (from 0.904 to 0.999

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The maceration duration and the addition of sulfur in the vinification process could not be fully correlated with the antimicrobial effects of the wines. This was also previously confirmed in several studies [6,12,14]. Further, the ethanol diluted to the level of concentration found in the wines (13 to 15%) showed no antimicrobial activity.…”
Section: Antimicrobial Activitysupporting
confidence: 83%
See 2 more Smart Citations
“…The maceration duration and the addition of sulfur in the vinification process could not be fully correlated with the antimicrobial effects of the wines. This was also previously confirmed in several studies [6,12,14]. Further, the ethanol diluted to the level of concentration found in the wines (13 to 15%) showed no antimicrobial activity.…”
Section: Antimicrobial Activitysupporting
confidence: 83%
“…The particular role of total phenolics remains unclear. In previous studies, it has been suggested that compounds such as flavonoids (quercetin and quercetin-3-glucoside) and monomeric anthocyanins might be used as biochemical markers that contribute to the antimicrobial activity of red wines [9,14]. Among wine phenolics, resveratrol has been particularly emphasized as a strong antimicrobial compound [34,41].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In different studies C. coum Miller subsp. coum extracts of flowers had an increased efficiency solely against C. albicans [ 98 , 99 ], highlighting the existing antibacterial differences even between similar genotypes. The potential antimicrobial activity of C. persicum Halios falbala (FC9) can be correlated with the total content of polyphenolic and flavonoid compounds that can act synergistically with the content of anthocyanins.…”
Section: Resultsmentioning
confidence: 99%
“…Multivariate analysis, such as the combination of cluster analysis and PCA, are techniques widely used for a precise classification of different extracts based on their chemical composition and bioactivities. PCA is the most commonly used method for performing multivariate analysis in flowers, leaves, and fruits of multiple plants [ 98 , 99 ], which is frequently compared with correlation coefficients [ 110 ].…”
Section: Resultsmentioning
confidence: 99%